25. End-to-end tests of the new Elekta gamma knife ICON. (December 2016) - Dorenlot, A.; Champoudry, J.
Abstract : Introduction: The objective of this study is to evaluate performance and accuracy of each part of the new Leksell Gamma Knife ICON. Methods: The evaluation was based on four criteria: quality of the image, dose due to the image (CBDI and dose distribution into the patient) mechanical performance, monitoring system (HDMM). The CBCT Image quality was evaluated using the Catphan 503 phantom (The Phantom Laboratory) coupled to MyQA software (IBA). The phantom was daily scanned with the two acquisition presets (high and low dose) over a period of two months. The contrast noise ratio (CNR), overall uniformity, scaling discrepancy, geometric distortion and spatial resolution were measured. The CBDI were measured with the two available presets (low and high dose) with a Raysafe X2 CT chamber and a CTDI phantom (The Phantom Laboratory). The dose distribution evaluation were evaluated by using thermoluminescent detectors (TLD) and an anthropomorphic head phantom RANDO (The Phantom Laboratory).The mechanical performances, consisting of comparisons between Leksell and real coordinates of four objects, have been evaluated with the Diode tool+ provided by Elekta. A series of 100 measurements enable us to quantify the repeatability and reproducibility of the system. The HDMM system was assessed using a micrometer screw on which we mounted a patient marker allowing movement visualization by the infrared cameras. Movements in three directions were applied and recognition assessed. Results: Image quality results are: CNR: 1.41 ± 0.1/2.24 ± 0.17 (low/high), overall uniformity: 83.14 ± 0.98/86.57 ± 0.66 (low/high). For the scaling discrepancy: 0.26 ± 0.20/0.21 ± 0.1 mm (low/high), the geometric distortion: 0.33 ± 0.05/0.21 ± 0.03 mm (low/high) and resolution space 0.49 ± 0.02/0.48 ± 0.01 lp/mm (low/high). CBDI values are 2.23 and 5.9 mGy (low/high). The dose distribution into the head phantom shows a large heterogeneity: doses measured are between 2.24 and 7.28 mGy when scanning with the high dose preset. The mechanical performance with the Diode Tool+ show us a maximum discrepancy of 0.17 ± 0.02 mm and the average manual measurements are between 0.16 and 0.19 ± 0.05 mm. The accuracy of the HDMM system was equal to 0.01 mm with a maximum error of 0.05 mm. Conclusions: The sum of these results demonstrates the overall quality of the new Leksell Gamma Knife ICON and offers the guarantee of high quality procedures for hypo fractionated and frameless treatment.